Comparing disciplinary engagement in global health research across the social sciences. (22nd March 2022) - Harris, Joseph; Shaffer, Jonathan D.
Abstract: Objectives: What did social science disciplines contribute to the study of global health before the coronavirus pandemic? This article compares the contributions of four major social science disciplines—anthropology, economics, political science, and sociology—to the study of global health. Methods: We assessed disciplinary contributions through analysis of Web of Science; disciplinary annual reviews; and each discipline's top two general focus journals, complemented by literature reviews. Results: Of the four disciplines, anthropology and economics have contributed relatively more in quantitative terms, although qualitative contributions have been refracted through the larger histories, methods, and theoretical concerns. Although interest in global health research has grown across the disciplines, only in anthropology has it achieved a measure of prominence in top journals. Conclusion: Cross‐disciplinary comparison draws out how each discipline approaches global health; which topics it studies; and the topic's centrality/marginality within the broader disciplines.